(untitled) (Bangladesh Journal of Microbiology, 2019)
Though Legionella pneumophila is an opportunistic pathogen, recent reports about multi drug resistance in L. pneumophila is alarming. Annotated whole genome provides a pool of information which is applied for therapeutic drug targets identification in pathogenic bacteria. Subtractive genomic analysis is a pragmatic approach to screen the essential proteins present in pathogen but absent in host. Phylogenetically closely related L. pneumophila str. Philadelphia and L. pneumophila str. ATCC43209 protein profiles were analyzed to identify putative drug targets. Paralogous duplicate profiles were primarily discarded using CD-hit suit. Six hundred and ninety one L. pneumophila str. Philadelphia and 690 L. pneumophila str. ATCC43209 human homologous proteins were excluded using blstP. Among the human non-homologous proteins, the essential proteins for bacteria were separated using DEG tool. For both strains, one hundred and nineteen essential proteins were marked which participate in various metabolic pathways. Among them 11 unique proteins were found. Beside it, 15 and 16 exposed surface proteins were present in strain Philadelphia and ATCC43209 respectively. These unique and cell surface proteins can be utilized for effective drug and vaccine targets. Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 102-107